Robert De Beaugrande’s Textual Standards And Its Impact On Understanding The Hadith Of Prophetic Medicine Of Talbīna - Muhammad Izuan Abd Gani; Asem Shahedeh Ali (Anka Publisher, 2024)
Non-Indexed Publication